2014
DOI: 10.1016/j.metabol.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and endothelin-1 mediated vasoconstrictor tone in overweight/obese adults

Abstract: Objective To determine whether endothelin (ET)-1 vasoconstrictor tone is greater in overweight and obese adults with the metabolic syndrome (MetS). Materials/Methods Forty overweight/obese middle-aged and older adults (age: 43-71 years; BMI: 25.1-36.9 kg/m2) were studied: 20 without MetS (13 M/7 F) and 20 with MetS (13 M/7 F). MetS was established according to NCEP ATP III guidelines. Forearm blood flow (FBF; plethysmography) responses to intra-arterial infusion of selective ETA receptor blockade (BQ-123; 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…For example, Schinzari, et al (Schinzari et al 2015) demonstrated that endothelium-dependent vasodilator dysfunction is worse in obese adults with MetS than obese adults without MetS. Moreover, we recently demonstrated (Rocha et al 2014) that MetS is associated with higher endothelin-1-mediated vasoconstrictor tone in obese adults. The results of the present study significantly extend these findings by demonstrating that endotheliumdependent vasodilation is markedly reduced in normal weight adults with MetS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, Schinzari, et al (Schinzari et al 2015) demonstrated that endothelium-dependent vasodilator dysfunction is worse in obese adults with MetS than obese adults without MetS. Moreover, we recently demonstrated (Rocha et al 2014) that MetS is associated with higher endothelin-1-mediated vasoconstrictor tone in obese adults. The results of the present study significantly extend these findings by demonstrating that endotheliumdependent vasodilation is markedly reduced in normal weight adults with MetS.…”
Section: Discussionmentioning
confidence: 59%
“…The mechanisms underlying the D r a f t increased CV risk with MetS are not fully understood, but endothelial dysfunction is considered a primary contributing factor (Suzuki et al 2008). In obese adults with MetS, endothelial vasomotor function, a key feature of endovascular health, is negatively affected (Schinzari et al 2010;Rocha et al 2014;Schinzari et al 2015). For example, Schinzari, et al (Schinzari et al 2015) demonstrated that endothelium-dependent vasodilator dysfunction is worse in obese adults with MetS than obese adults without MetS.…”
Section: Discussionmentioning
confidence: 99%
“…The prominent role for obesity fits into a recently proposed paradigm whereby metabolic co‐morbidities drive LV remodelling and dysfunction in HFPEF and into earlier observations that metabolic syndrome reinforces pulmonary venous hypertension . The former was explained by deficient myocardial microvascular nitric oxide (NO)/cGMP signalling, and the latter by excessive pulmonary venous endothelin‐1‐mediated vasoconstrictor tone . Both derive from a deranged Yin–Yang between endothelial NO and endothelin‐1 in metabolic disturbances .…”
Section: Characteristics Of the Misclassified Pulmonary Hypertension mentioning
confidence: 72%
“…11 The former was explained by deficient myocardial microvascular nitric oxide (NO)/cGMP signalling, 12 and the latter by excessive pulmonary venous endothelin-1-mediated vasoconstrictor tone. 13 Both derive from a deranged Yin-Yang between endothelial NO and endothelin-1 in metabolic disturbances. 14 The clinical characteristics of the misclassified PHT provide the readers of the journal with an important 'take-home' message, namely that overweight/obese patients with PHT and normal PAWP need to undergo invasive exercise testing or a volume infusion challenge before they can be classified as pre-capillary PHT group 1 patients.…”
Section: Characteristics Of the Misclassified Pulmonary Hypertension mentioning
confidence: 99%
“…Hypertension, a disorder associated with structural and functional vascular alterations, has been recognized as a major risk to cardiovascular health (1). As hypertension is correlated with coronary artery disease, left ventricular hypertrophy, congestive heart failure, obesity, hyperlipidemia, diabetes and cerebrovascular complications, it represents the biggest single contributor to the global burden of disease and to global mortality (1)(2)(3)(4). Recent studies have demonstrated that some gene variants may be involved in hypertension (2,3).…”
Section: Introductionmentioning
confidence: 99%